Crystal structure study of a vanadium (III) complex containing a neopentanediamminetetraacetate ligand - Robles, Julita Climaco (Animo Repository, 1993)
The crystal structure of the vanadium(III) complex, Na[V(npdta)], was determined by single crystal x-ray diffraction techniques. The complex, NapV(npdta)] belongs to the monoclinic crystal system of the space group A a (No. 9), where a = 12.026(1) A b = 12.748(1) A c = 10.580(1) A B = 93.91 degrees V = 1618.1(2) A3 Z = 4 calculated d = 1.66 g/cm3 and Rw = 0.039. The crystal structure analysis revealed that the hexadentate ligand coordinates to vanadium(III) in a distorted octahedral manner. The acqueous solution of the complex was found to exhibit thermochromism with an isosbestic point at 700 nm.